EFFECTIVENESS OF RISK MANAGEMENT IN NIGERIA’S MANUFACTURING ENTERPRISES - Kehinde Olaiya; Olusola Olowofela; Mayowa Ariyibi (Acta Economica)
This study seeks to examine the effectiveness of enterprise risk management (ERM) implementation in the Nigerian manufacturing sector. The objective of this study is to analyze the risks faced by manufacturing firms in Nigeria and to recommend actions to address and reduce anticipated hazards. This research used both inferential and descriptive statistics to examine the effectiveness of ERM application in Nigeria’s manufacturing sector. The data for this study were collected from the financial statements of manufacturing firms and other relevant publications by manufacturing firms in Nigeria from 2016 to 2020. The study found that ERM has a positive relationship with financial performance indicators such as return on investment, dividend, earnings per share, market capitalization, price earnings ratio, and dividend per share. The study recommends that manufacturing companies in Nigeria should implement ERM as an ongoing activity to improve their risk management practices, enhance their effectiveness, and ensure their long-term sustainability. This study contributes to the literature on ERM implementation in the Nigerian manufacturing sector and provides valuable insights for policymakers, regulators, and business managers.